Interlayer Separation in Graphene Paper Comprising Electrochemically Exfoliated Graphene - Dang Du Nguyen; TaeGyeong Lim; Soomook Lim; Ji Won Suk (Nanomaterials, 2021)
The emergence of graphene paper comprising well-stacked graphene flakes has promoted the application of graphene-based materials in diverse fields such as energy storage devices, membrane desalination, and actuators. The fundamental properties of graphene paper such as mechanical, electrical, and thermal properties are critical to the design and fabrication of paper-based devices. In this study, the interlayer interactions in graphene paper were investigated by double cantilever beam (DCB) fracture tests. Graphene papers fabricated by flow-directed stacking of electrochemically exfoliated few-layer graphene flakes were mechanically separated into two parts, which generated force-displacement responses of the DCB sample. The analysis based on fracture mechanics revealed that the interlayer separation energy of the graphene paper was 9.83 ± 0.06 J/m2. The results provided a fundamental understanding of the interfacial properties of graphene papers, which will be useful for developing paper-based devices with mechanical integrity.